2022
DOI: 10.3389/fped.2022.865057
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcomes of preterm infants receiving non-invasive high-frequency oscillatory ventilation

Abstract: ObjectiveTo investigate the clinical outcomes of preterm infants who received non-invasive high-frequency oscillatory ventilation following extubation in a neonatal intensive care unit.MethodsInfants born between 25 and 34 weeks of gestation with a birth weight of <1,500 g, who were admitted into the neonatal intensive care unit of Guangxi Maternal and Child Health Hospital, Nanning, Guangxi, China, requiring mechanical ventilation on admission were randomized to the non-invasive high-frequency ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Five articles potentially satisfied the included criteria by reviewing the titles and abstracts. Finally, four eligible articles were included for further analysis, [16][17][18][19] and one article was excluded because the primary outcome was the rates of long-term respiratory morbidities and neurodevelopmental impairment in preterm infants 20 (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Five articles potentially satisfied the included criteria by reviewing the titles and abstracts. Finally, four eligible articles were included for further analysis, [16][17][18][19] and one article was excluded because the primary outcome was the rates of long-term respiratory morbidities and neurodevelopmental impairment in preterm infants 20 (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…A follow-up study aiming to explore the long-term safety of NHFOV demonstrated that preterm VLBW infants who received NHFOV after their first extubation at birth, compared with NIPPV or CPAP, did not differ significantly in the number of episodes of bronchitis, pneumonia, wheezing and re-admission rates at 24 months corrected age. In addition, pulmonary function tests and the incidence of neurodevelopmental impairment at 12 and 24 months corrected age were similar between the groups (41). The study, however, had a relatively small sample size (n = 139 infants) and low follow up rate (113 out of 139 infants at 12 months and 110 out of 139 infants at 24 months corrected age) and therefore further evidence is required.…”
Section: Nasal High-frequency Oscillatory Ventilation (Nhfov)mentioning
confidence: 89%
“…There is also an urgent need for clear criteria to define nHFOV failure. As regards the information on the outcomes of the infants supported using nHFOV, up to now, there are few studies suggesting that similar to HFOV, there is no adverse effect on cerebral hemodynamics [68] and no adverse effects compared to NCPAP and NIPPV after extubation [69]. Indeed, we need more studies in this respect.…”
Section: Discussionmentioning
confidence: 99%